HAPPINESS OF EVOCATION - Dumitru Batîr (Chemistry Journal of Moldova: General, Industrial and Ecological Chemistry, 2013)
The author attempts a synthetic reconstitution of the life and activity of a prominent scientist, professor and man of culture Victor Isac (1943-1995), Doctor Habilitatus in chemistry, university professor, State Prize Laureate of Republic of Moldova in Science, Technology and the Production (post-mortem), author of more than 220 scientific works, including 14 monographs, textbooks, studies, highly appreciated in the country and abroad, and holder of patents related to ecological science.